The Relationship of HbA1c Levels with Blood Edition Rate Values in Type 2 Diabetes Mellitus Patients - Nili Nataliya; Sulasmi Sulasmi; Tasrif Ahmad (Indonesian Journal of Global Health Research, 2023)
Diabetes Mellitus is a group of metabolic disorders characterized by increased blood glucose as a result of impaired insulin production or impaired insulin performance or both. In uncontrolled diabetes patients, it is characterized by high HbA1c levels and causes various complications, both acute and chronic complications. Hyperglycemia affects the inflammatory response and the body's immunity to infection which results in a decrease in the function of the body's immune cells, the infection can manifest more severely. Blood sedimentation rate, one of the benefits of the examination is to find out acute inflammatory reactions both local and systemic as well as inflammation associated with chronic disease. Based on the above, it can be stated that checking HbA1c levels and ESR values can be the first step to prevent DM complications. The aim of this study was to determine the relationship between HbA1c levels and ESR values in type-2 DM patients who underwent HbA1c examinations at the Prodia Clinic laboratory in Sorong. The method used is observational analytic with a cross sectional approach. Data were taken from 35 Prolanis patients with type-2 DM by purposive sampling. Venous blood samples were used, HbA1c levels were checked with the Bio-Rad D10 and LED with the Westergreen method. The data were analyzed using the Spearman correlation test, with a significant p-value of 0.002 (<0.05) with a correlation coefficient (r) of 0.506. It can be concluded that there is a significant relationship between HbA1c levels and ESR values in type 2 Diabetes Mellitus patients with a moderate level of relationship.